The Effectiveness of Using Retelling Story Technique Through Pictures Series Media on Speaking Ability of Students of Grade 10th Mariana Catholic High School Medan - Cynthia Magdalena Marpaung; Carolina Pakpahan; Rina Octavia Simarmata (PT. Pusmedia Group Indonesia, 2025)
This research was motivated because grade X students of Mariana Catholic High School Medan experienced difficulties in English speaking skills characterized by lack of confidence, vocabulary limitations, and reluctance to speak in front of the class. This study aims to analyze whether retelling techniques using continuous image media significantly affect the speaking ability of Grade 10 students at Mariana Catholic High School Medan. A quasi-experimental design with pre-test and post-test methods was employed to observe students ' speech skills before and after the application of the retelling techniques. The sample consisted of 30 Grade10 students. Data were collected through speaking tests to evaluate students' abilities. The results indicated an increase in the average score of students ' speaking ability after applying the retelling techniques, with the experimental group's post-test average score at 74.9. From the results of the t-test that had been conducted, a t-value of 2.81 was obtained. This value was higher than the commonly used significance limit of 2.048 at the 0.05 level. This indicates that Ho is rejected and Ha is accepted , concluding that the use of retelling techniques with continuous image media significantly impact the speaking ability of Grade 10 students at Mariana Catholic High School Medan